Gait Speed Trajectory During the Six-Minute Walk Test in Multiple Sclerosis: A Measure of Walking Endurance - Chen, Shanshan; Sierra, Salvador; Shin, Yongyun; Goldman, Myla D. (Frontiers in Neurology, 2021)
Background: The six-minute walk (6MW) test is a validated assessment method in Multiple Sclerosis (MS) research. While the total distance covered during six minutes (6MWTD) is often used as the standard measurement of gait capacity (i.e. the maximum distance one can achieve), we hypothesize that endurance (i.e. ability to maintain speed over a prolonged time) can be inferred by the gait speed trajectory (GST) during the 6MW test (6MWGST). Objective: To characterize group differences in 6MWGST between MS patients and healthy controls (HCs), and to assess information added by 6MWGST for discerning between MS patients and HCs. Methods: We performed a secondary data analysis on a cross-sectional cohort of 40 MS and 20 HC subjects with three repeated 6MW tests. We modeled 6MWGST using a linear mixed-effects model with time in minutes and replicated walks nested within individuals. We compared the discernibility of 6MWGST with that of conventional metrics using likelihood ratio tests and receiver operating characteristic analysis (ROC) on logistic regression models. Results: MS subjects showed a concave, quadratic GST during 6MW tests, slowing down more than the HC subjects, especially at the very beginning of 6MW tests (by 4.5 feet/minute2, or 1.4 meters/minute2). Despite accelerating at the end of the 6MW, MS subjects were unable to attain or surpass their initial 6MW gait speeds. 6MWGST added useful information (p=0.002) to the conventional metrics (e.g. 6MWTD) for discerning between MS and HC subjects, and increased the area under the ROC curve from 0.83 to 0.93 (p=0.037). Conclusions: The distinctive 6MWGST pattern of MS patients provided increased discernibility compared with currently used gait metrics. Both gait capacity measured by the 6MWTD, and gait endurance measured by parameters of 6MWGST, are significant functional indicators for the MS population.